Adsorptive Removal of Reactive Yellow 15 from Aqueous Solution by Coconut Coir Activated Carbon - Taimur Khan; Shamsul Rahman Mohamed Kutty; Malay Chaudhuri (Adsorption Science & Technology)
Activated carbon was prepared from coconut coir and its ability to adsorb Reactive Yellow 15 (RY15) dye examined. Batch adsorption tests showed that the extent of dye adsorption depended on the initial dye concentration, the contact time and the pH value of the solution. Equilibrium adsorption was attained within 240 min, with maximum adsorption occurring at a pH value of 2. The adsorption capacity of the activated carbon towards the dye was evaluated and compared with that of a commercial activated carbon. Equilibrium adsorption data for the coconut coir activated carbon (CCAC) and the commercial activated carbon (CAC) were well described by the Langmuir and Freundlich isotherm models, and indicated the higher adsorption capacity of CCAC. The adsorption of RY15 by CCAC and CAC followed pseudo-second-order kinetics. The results indicate that activated carbon prepared from coconut coir is more effective than CAC for the adsorption of RY15. Hence, CCAC would be a suitable substitute for CAC in the removal of Reactive dyes from aqueous solution.